1999
DOI: 10.1074/jbc.274.20.14176
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Ester-induced Disruption of the CD4-Lck Complex Occurs within a Detergent-resistant Microdomain of the Plasma Membrane

Abstract: Recent studies have highlighted the existence of discrete microdomains at the cell surface that are distinct from caveolae. The function of these microdomains remains unknown. However, recent evidence suggests that they may participate in a subset of transmembrane signaling events. In hematopoietic cells, these low density Triton-insoluble (LDTI) microdomains (also called caveolae-related domains) are dramatically enriched in signaling molecules, such as cell surface receptors (CD4 and CD55), Src family tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 68 publications
7
65
0
1
Order By: Relevance
“…Briefly, 2 ϫ 10 8 cells were suspended in 1 ml of lysis buffer containing 1% Triton-X-100, 10 mM Tris-HCl (pH 7.5), 150 mM NaCl, 5 mM EDTA, 1 mM NaVO 4 , and 75 units of aprotinin and allowed to stand for 20 min. The cell suspension was mechanically disrupted by Dounce homogenization (10 strokes).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, 2 ϫ 10 8 cells were suspended in 1 ml of lysis buffer containing 1% Triton-X-100, 10 mM Tris-HCl (pH 7.5), 150 mM NaCl, 5 mM EDTA, 1 mM NaVO 4 , and 75 units of aprotinin and allowed to stand for 20 min. The cell suspension was mechanically disrupted by Dounce homogenization (10 strokes).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we studied the glycosphingolipid composition of these specialized portions of plasma membrane in human peripheral blood lymphocytes (7), demonstrating by high performance thin layer chromatography, gas chromatographic and mass spectrometric analysis that GM3 represents one of the main markers of microdomains in these cells. Minor components are sialosyl paragloboside (NeuAc-nLac 4 Cer), migrating between GM3 and GM1, sialosyl lactohexaosyl ceramide, and disialoganglioside GD3 (2,10,11). Gangliosides may be involved in modulating signal transduction, mainly by interaction with specific signal transducer molecules detected in these domains (8), such as p56 lck (12) or Zap-70 (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, gp160 also induced a 3-fold increase in PKC␤I amount, which resulted in the enrichment of the Triton-insoluble (150%) fraction. Very recently, it has been proposed that the Triton-insoluble fraction contains lipid components of the rafts membrane microdomains (47) and, therefore, might represent membrane-bound protein. Accordingly, Nixon and McPhail (48) have recently shown that upon stimulation the levels of PKC␣ and -␤I increased in the Triton-insoluble fraction.…”
Section: Reduction In the Crac Current Of Jurkat Cells After Gp160mentioning
confidence: 99%
“…The interpretation of gradient centrifugation experiments remains controversial. There is evidence that detergents may force associations between components that are not colocalized in intact cells (Mayor and Maxfield, 1995), and fractionation results are known to be dramatically altered by varying the concentration of Triton X-100 (Field et al, 1999;Parolini et al, 1999), by use of alternative detergents (Montixi et al, 1998;Surviladze et al, 1998) or by omission of detergent altogether (Ilangumaran et al., 1999;Harder and Kuhn, 2000;Surviladze et al, 2001). Methods to observe membrane segregation in situ have also generated controversy.…”
Section: Introductionmentioning
confidence: 99%